Resemblance of Dinner Meal Consumption among Mother and Preschool-Aged Child Dyads from Families with Limited Incomes - Nicklas, Theresa A.; O’Neil, Carol E.; Hughes, Sheryl O.; Liu, Yan (International Journal of Child Health and Nutrition, 2013)
Parents’ eating habits are associated with food and nutrient intake of their children; yet, the associations have not always been very strong. The objective of this study was to expand the current literature to include an examination of resemblance in intakes of foods, within the context of a meal, among mother and preschool-aged child dyads from families of limited incomes. Mother-child dyads (n=112; 41% Hispanic and 59% African-American) participated in the study. During the two home observations of each mother-child dyad, a digital photography method plus actual weighing of plate waste was used to assess the amount of food served and consumed by the mothers and children. There were significant correlations between the mother-child dyad intakes of food/beverages consumed at the dinner meal; ranging from 0.298 (total beverages, p<0.01) to 0.687 (100% fruit juice or milk, p<0.01). There was a significant linear association between the amount of total food/beverages served and the amount consumed for both the mothers (R2=0.72, p<0.0001) and the children (R2=0.55, p<0.0001). Mothers-children who were served larger amounts of total food/beverages consumed more. There was a positive association (p<0.05) between the amount of total energy consumed in the mother-child dyads. Portion sizes may be an important strategy that can be used by parents to promote intake of fruits and vegetables and to decrease intake of energy-dense foods. It is important that food and nutrition professionals provide the guidance needed that encourages intake of major food groups in mothers so they can model healthier food consumption behaviors for their children.